Geological Modeling for Yamama Formation in Abu Amood Oil Field - Nasser , Medhat E.; Al-Jawed , Sameer N.; Hassan , Mushtak F. (Iraqi Journal of Science, 2021)
3D geological model of a simple petroleum reservoir for Yamama Formation hasbeen built in Abu Amood Oil Field using Petrel software, which is a product ofSchlumberger. This model contains the structure, stratigraphy and reservoirproperties (porosity and water saturation) in three directions(X, Y and Z).Geologicmodeling is an applied science of creating computerized representations of portionsof the earth’s crust, especially oil and gas fields.Yamama Formation in Abu Amood Oil Field is divided into thirteen zones byusing well logs and their petrophysical properties, six of which are reservoir zones.From the top of the formation these six zones are: (YB-1, YB-2, YB-3, YC-1, YC-2and YC-3). These reservoir zones are separated from each other by barriers, whichare of little or no porosity.